2014
DOI: 10.1177/0269215513514983
|View full text |Cite
|
Sign up to set email alerts
|

Does botulinum toxin injection site determine outcome in post-stroke plantarflexion spasticity? Comparison study of two injection sites in the gastrocnemius muscle: a randomized double-blind controlled trial

Abstract: Botulinum toxin A injection was associated with a significant improvement from baseline to week 8 in both treatment groups, however, no significant difference between the 2 groups was observed, based on the electrophysiological and clinical parameters employed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…found that the efficacy of MEP‐targeted BoNT‐A injections was superior to that of non‐targeted injections in spastic elbow flexors of adults post stroke. In a recent study of the same subject group, Im et al . could not replicate these results for the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…found that the efficacy of MEP‐targeted BoNT‐A injections was superior to that of non‐targeted injections in spastic elbow flexors of adults post stroke. In a recent study of the same subject group, Im et al . could not replicate these results for the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 83%
“…In order to understand whether or not the specific site of gracilis muscle injection influences the effects of BoNT‐A on muscle spasticity, a double‐blind, randomized controlled trial was set up to compare two injection techniques: MEP‐targeted injection and the widely used proximal injection technique . Previous studies comparing muscle injection sites have used surface electromyography (sEMG) during maximum voluntary contractions (MVCs) to record the denervation effects of BoNT‐A . However, there have been no studies reporting the effects of injection site on spasticity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other current treatments, it must to be noted that EOAz enhanced contractile performance after a short period of 10 daily dermal applications. The golden standard treatment with botulinum toxin A induced similar (discrete) changes in sEMG recordings of spastic gastrocnemius after 8-week administration, although the clinical parameters were considerably improved [39]. It indicates that small modifications in sEMG can reflect important functional recovery.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental studies used the ABILOCO as an outcome measure and reported changes in scores above 0.55 logit. Im et al evaluated the effects of botulinum toxin injection in two sites of the lower limbs of stroke patients and found mean changes of 1.7 and 1.9 logits ( P < .01), respectively. Caty et al investigated the effects of botulinum toxin injections in several spastic muscles of patients with chronic stroke who had stiff knee gait and found increases in scores ranging from 2.2 to 3.2 logits ( P = .03).…”
Section: Discussionmentioning
confidence: 99%